Parathyroid Adenoma: an experience in BIRDEM General Hospital - Mahbub, Shawhely; Biswas, Sudhangshu Shekhar; Dey, Badhon Kumar; Alam, Md Shariful; Hoq, Jahirul (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Parathyroid adenoma is most commonly associated with primary hyperparathyroidism which leads to hypercalcaemia. Hypercalcaemia results in multiple stone formation in Kidney and biliary tract which indicates surgical removal of tumor. Perioperative management of patient is essential to prevent mortality and morbidity. The purpose of this study is to analyze a case series of patient having parathyroid adenoma with difficulties, to localize the adenoma and to take the measures to maintain the normal level of calcium in pre, per and postoperative period. Methods: This retrospective study was carried out in BIRDEM General Hospital and Ibrahim Medical College from May 2017 to December 2019. 14 patients who were diagnosed as primary hyperparathyroidism due to parathyroid adenoma who had been managed at the BIRDEM General Hospital, Dhaka, Bangladesh from May 2017 to December 2019 were reviewed and included. Result: Among 14 patients 8 were female and 6 male (M: F=3:4). Age ranges from 26 to 71 years with mean age was 52 years. Serum PTH were above normal (>65 pg/ml) in all cases. Serum calcium level were above normal in 12 cases (85.71 %) and 2 (14.29%) had normal levels. Serum phosphate levels were within normal range. Excision of adenoma done in all cases which were confirmed by frozen section per-operatively. None of our patients develop any complication during and after surgery Conclusion: Successful management of parathyroid adenoma requires combined skills of surgeons, endocrinologists, anesthesiologists and pathologists. Improvement after operation is quite remarkable and rewarding. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 44-51